Association of biomarkers in pre-invasive and invasive cervical carcinoma - Meljanac Salopek, Kristina (Array, 2019)
Introduction: Various reports suggest linkage of protein expression to HPV status in cervical carcinomas. The aim of this study was to determine a possible association between HPV type, protein expression and DNA content in both preinvasive (CIN III) and invasive squamous cell carcinoma (SCC) of the cervix, as well as differences between the studied groups in these parameters. Materials and methods: Sections of formalin-fixed paraffin-embedded tumor tissue from 47 cases of CIN III and 60 cases of invasive SCC of the cervix were subjected to HPV genotyping using LiPA (Line immuno-probe assay) and Flow cytometry for DNA content analysis. Also, immunohistochemical staining was performed. Obtained data were analyzed in SPSS using the Chi square test. Results: The major difference (p=0.007) between CIN III and invasive SCC of the cervix was found in DNA content - more aneuploid and tetraploid cases in invasive SCC of the cervix compared to CIN III. Although we observed a similar distribution of studied parameters in both groups, no statistically significant association was found between these parameters, except for p53 and pRb (p=0.018). Conclusion: The studied groups differ in DNA content. A significant association between analyzed parameters was observed in Invasive SCC of the cervix between p53 and pRb expression.